2005
DOI: 10.1016/j.bbmt.2005.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Mucositis after Allogeneic Hematopoietic Stem Cell Transplantation: A Cohort Study of Methotrexate- and Non-Methotrexate-Containing Graft-versus-Host Disease Prophylaxis Regimens

Abstract: Oral mucositis occurs in up to 75% of recipients of high-dose chemoradiotherapy conditioning regimens used for allogeneic hematopoietic stem cell transplantation (HSCT). As a result of mucositis, narcotic analgesia and total parenteral nutrition (TPN) are commonly required after HSCT. Methotrexate, an antiproliferative graft-versus-host disease (GVHD) prophylaxis agent, impairs mucosal regeneration and worsens and prolongs mucositis. We assessed the effect of substituting sirolimus for methotrexate as GVHD pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 26 publications
5
101
0
5
Order By: Relevance
“…MTX-containing GVHD prophylaxis are known to be associated with a higher incidence of stomatitis. 25 Apart from CMV reactivation, there did not appear to be a difference in overall rates of infectious complications between the alemtuzumab and control groups. Alemtuzumab-treated patients experienced significantly more episodes of early and late CMV reactivation than control patients ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…MTX-containing GVHD prophylaxis are known to be associated with a higher incidence of stomatitis. 25 Apart from CMV reactivation, there did not appear to be a difference in overall rates of infectious complications between the alemtuzumab and control groups. Alemtuzumab-treated patients experienced significantly more episodes of early and late CMV reactivation than control patients ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is well know that MTX has several potentially relevant toxicities (pulmonary, hepatic, gastrointestinal and hematopoietic toxicity). 6,7 In addition, we recently reported that MTX is a risk factor for early acute renal failure, which may contribute to early and late NRM in allo-RIC patients. 8 The higher rate of mucositis, the trend to higher rate of neutropenic fever in addition to a more frequent early non-related GVHD deaths, observed in this group of patients, may support the higher toxicity of MTX.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, MTX delays hematopoietic engraftment, worsens oral mucositis and may be associated with pulmonary and renal toxicity after allo-HSCT. [5][6][7][8] In patients undergoing allo-RIC, reducing procedure-related toxicities may be of great importance, as these patients usually have greater comorbidities. Thus, in an attempt to reduce any MTX-associated toxicities, mycophenolate mofetil (MMF) has replaced MTX in RIC regimens in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common complications of this regimen is oral mucositis (OM) and literature shows that 75% of allogeneic hematopoietic SCT recipients may develop severe OM. 2 Probable consequences of OM include pain, increased risk of infection, impaired nutritional intake and prolonged hospitalization. 3 OM is characterized by mucosal damage ranging from mild inflammation to extensive ulceration.…”
Section: Introductionmentioning
confidence: 99%